PENGEMBANGAN MEDIA PEMBELAJARAN 16 TENSES BAHASA INGGRIS BERBASIS ANDROID - Nelly Rosaline; I ketut Setiawan (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2021)
Indonesia is ranked 74 out of 100 countries and is in the low category in the EF EPI 2020 (Education First English Proficiency Index). Grammar and tenses are the basic components in English. This study aims to design, create, and implement learning 16 English tenses for college students. The learning media will provide tables and explanations of 16 tenses in English, sentence examples and exercises in the form of quizzes equipped with pronunciation sentences to practice listening skills. The data collection methods used were interviews, questionnaires, documentation and literature. The application is made based on Android that can be downloaded on Google Play. Based on the results of 50 college students’ evaluation, it stated that in terms of material, 91,9% was easy to understand, while in terms of UI, 97.6% was interesting to use, and in terms of UX, 90,8% was easy to use. Based on the interview results of 3 English lecturers in this study, it can be concluded that 83,7% of the material is suitable for the college student level, while in terms of UI, 86.7% is Demandia, Vol. 06 No. 02 (September 2021) 278 interesting to use, and in terms of UX. 91.7% is easy and recommended to be used as a supporting media for learning English at STMIK STIKOM Indonesia. Keywords: Learning media, English Tenses, Android application